Totes N Thing / Fazreen Izleen Rafidi and Anis Syazwana Mohamad Azhar - Rafidi, Fazreen Izleen; Mohamad Azhar, Anis Syazwana (2022)
Totes N Thing started when the both of us wanted to make some income to support us financially while we were still studying. We choose to start a business selling tote bags because we find it a burden for students to carry our stuff but still want to be stylish. It is difficult to find a trendy bag that is practical to match our outfits. The brand name "Totes 'n' Thing' is chosen because it is short and simple, meaning it will be easier for people to remember and is is also wonderfully quirky. The name also shows the customer that we will expand our business into other things to in the future instead of just focusing on one product. Our form of business is a partnership owned by both of us, Fazreen Izleen and Anis Syazwana. For the moment, our business only takes place at our home to reduce the cost of rental since we do not have a lot of financial support yet.